Faith-Based Digital Economy and Muslim Community Empowerment: A Socio-Religious Analysis of NUJEK as a Nahdlatul Ulama Affiliated Startup in Indonesia - Purwanto, Andi; Bariroh, Arrizqah; Nurhayati, Nurhayati (Potret Pemikiran, 2025)
This study examines the socio-religious dimensions of faith-based digital startups in Indonesia by analyzing NUJEK, a transportation platform affiliated with Nahdlatul Ulama. The emergence of such platforms reflects the integration of Islamic values into digital economic practices, particularly in fostering Muslim community empowerment. This research aims to explore how NUJEK operationalizes Islamic economic principles and contributes to socio-religious cohesion within the Nahdliyin community. This study employs a qualitative approach combining a systematic literature review and semi-structured interviews with NUJEK users and driver-partners. The analysis is guided by Islamic economic frameworks, including maqashid al-shariah, ta’awun, and maslahah, as well as socio-religious perspectives on community-based economic practices. The findings reveal that NUJEK functions not only as a digital service provider but also as a medium of Islamic social enterprise that strengthens community solidarity and economic inclusion. The integration of religious values enhances trust, encourages mutual cooperation, and supports the empowerment of local Muslim communities. The findings reveal that NUJEK functions not only as a digital service provider but also as a medium of Islamic social enterprise that strengthens community solidarity and economic inclusion. The integration of religious values enhances trust, encourages mutual cooperation, and supports the empowerment of local Muslim communities. This study contributes to the discourse on Islamic digital economy by highlighting the role of faith-based startups as instruments of socio-religious transformation and community empowerment.